The Ifluence Of Motivation, Leadership Style, Work Competence On Performance With Job Satisfaction As A Mediating Variable At The Fakhira Clinic - Anna, Anna Tamara; Tanuwijaya, Justine (JURNAL EKBIS, 2023)
The purpose of this study is to analyze the influence of motivation, leadership style, work competence on performance with job satisfaction as a mediating variabel at Fakhira Clinic in Sawah Lunto, Al-Barkah, Menteng Wadas, and Pesanggrahan. Data was collected on 125 respondents through distributing questionnaires using the census method. The technique used to analyze this research is an instrumental test in the form of validity and reliability tests. Hypothesis testing is processed using smartPLS 3.0. The results of hypothesis testing in this study show that there is an influence of leadership style and work competence on job satisfaction, there is an effect of job satisfaction on performance, and there is an influence of leadership style and work competence on performance which is mediated by job satisfaction. This research was only conducted in four branches in Sawah Lunto, Al-Barkah, Menteng Wadas, Pesanggrahan, and research variables used in this study only motivation, leadership style, work competence, and performance.